House-Hold Hints & Handy Tips - Published by Reader's Digest Association (New York Reader's Digest Association, 1988)
At head of title: Reader's Digest. Hints and tips for household problems.
Include Color Illustrations and Index
Keywords: Home economics -- Do-it-yourself work